Gakkel Ridge plagioclase and olivine mineral and melt inclusion analyses - Bennett, Emma; Jenner, Frances; Millet, Marc-Alban; Cashman, Katharine; Lissenberg, C (IEDA: EarthChem Library, 2019)
Abstract: The depth of crystallisation within mid-ocean ridge magma plumbing systems can be constrained using the volatile content of melt inclusions. Here the volatile-, trace- and major-element compositions of both olivine- and plagioclase-hosted melt inclusions from the Gakkel Ridge (Arctic Ocean) are presented. Host mineral major elements are also presented and were used to undertake melt inclusion post-entrapment crystallisation corrections. Other Description: Bennett, E., Jenner, F., Millet, A-B., Cashman, K., Lissenberg, C., 2019, Deep roots for mid-ocean ridge volcanoes revealed by plagioclase-hosted melt inclusions, Nature, 572 (235-239)